Analisis Potensi Penerimaan Zakat Melalui E-Commerce Pada Masa Pandemi Covid-19 - Hasanah, Uswatun (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Padangsidimpuan, 2021)
The potential for receiving zakat nationally before and during the Covid-19 pandemic is still enormous, while its realization is still very far from expectations. The National Amil Zakat Agency (BAZNAS) does is by utilizing the Digital Platform, including the commercial platform, which is collaborating with e-commerce (Bukalapak, Shoppee, Lazada, Blibli, JD.id, Tokopedia, Mataharimall.com and Elevenia). During the Covid-19 Pandemic, the increase in online zakat acceptance, primarily through e-commerce, increased sharply in line with changes in people's lifestyles. This situation has a huge potential to develop a system according to the needs of muzaki in optimizing the acceptance of zakat online, primarily through e-commerce. Keyword: Potensi, Penerimaan Zakat, E-commerce